2011
DOI: 10.1186/1471-2458-11-29
|View full text |Cite
|
Sign up to set email alerts
|

Suffering in silence: consequences of sexual violence within marriage among young women in Nepal

Abstract: BackgroundDespite the grave consequences of sexual violence, and it's persistence both within and outside marriages, this subject has received relatively little attention from researchers, policy makers, and programme managers in Nepal. This paper explores the definition of sexual violence and its various forms and consequences as reported by young married women in Nepal. In addition, it describes the coping mechanisms used by young married women to avoid sexual violence perpetrated against them by their husba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
48
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(59 citation statements)
references
References 18 publications
9
48
1
1
Order By: Relevance
“…This in turn may lead to sexual abuse. Furthermore, Puri and colleagues found that 8 out of 15 women who refused to have intercourse with their husbands were beaten [41]. Being beaten or threatened with violence when not obeying their husbands was also reported by women in the present study.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This in turn may lead to sexual abuse. Furthermore, Puri and colleagues found that 8 out of 15 women who refused to have intercourse with their husbands were beaten [41]. Being beaten or threatened with violence when not obeying their husbands was also reported by women in the present study.…”
Section: Discussionsupporting
confidence: 62%
“…No or little interspousal communication and low autonomy of women were associated with violence against women [16]. Other studies that investigated sexual violence against young married women found a similar prevalence (49%) [18, 41]. Lamichhane and colleagues associated women's lower status in family and society with violence against women, particularly young women in rural Nepal [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, migration of husbands and partners can have an impact on the mental health and suicide risk of the women staying behind [29].…”
Section: High Rate Of Male Migrationmentioning
confidence: 99%
“…The following were the 10 most frequently list acts and behaviours of their partners defined as sexual violence by the respondents. 10  Sex against partner"s wishes  Sex during illness  Forced sex after consuming alcohol  Sex during menstruation  Physical or verbal abuse or threats following refusal of sex  Sex after delivery/when baby is small  Sex in spite of being tired  Unwanted sexual touch  Extramarital sexual relationship  Forced sex.…”
mentioning
confidence: 99%